A DNA structural alphabet provides new insight into DNA flexibility. Issue 1 (26th January 2018) - Schneider, Bohdan; Božíková, Paulína; Nečasová, Iva; Čech, Petr; Svozil, Daniel; Černý, Jiří
Abstract : Large deformations of the DNA double helix induced by interactions with proteins and small molecules are necessary to support the biological function of DNA. Here, the software tools available athttps://dnatco.org that classify the dinucleotide building blocks into 44 distinct structural classes and 11 letters of a first DNA structural alphabet are presented and are used to analyze several prototypical DNA structures. Abstract : DNA is a structurally plastic molecule, and its biological function is enabled by adaptation to its binding partners. To identify the DNA structural polymorphisms that are possible in such adaptations, the dinucleotide structures of 60 000 DNA steps from sequentially nonredundant crystal structures were classified and an automated protocol assigning 44 distinct structural (conformational) classes called NtC (for Nucleotide Conformers) was developed. To further facilitate understanding of the DNA structure, the NtC were assembled into the DNA structural alphabet CANA (Conformational Alphabet of Nucleic Acids) and the projection of CANA onto the graphical representation of the molecular structure was proposed. The NtC classification was used to define a validation score called confal, which quantifies the conformity between an analyzed structure and the geometries of NtC. NtC and CANA assignment were applied to analyze the structural properties of typical DNA structures such as Dickerson–Drew dodecamers, guanine quadruplexes and structural models based on fibre diffraction. NtC, CANA and confal assignment, which is accessible at the websitehttps://dnatco.org, allows the quantitative assessment and validation of DNA structures and their subsequent analysis by means of pseudo‐sequence alignment. An animated Interactive 3D Complement (I3DC) is available in Proteopedia athttp://proteopedia.org/w/Journal:Acta_Cryst_D:2 .